2021
DOI: 10.1007/s11255-021-02976-7
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the kidney: time to take a closer look

Abstract: Although coronavirus disease (COVID-19) is primarily a respiratory disease, the kidney may be among the target organs of infection with severe acute respiratory syndrome coronavirus 2 (SARS-COV-2). Independently of baseline kidney function, acute kidney injury (AKI) is a common complication of COVID-19, associated with increased mortality and morbidity. Most frequently, COVID-19 causes acute tubular necrosis; however, in some cases, collapsing focal segmental glomerulosclerosis and direct viral tropism of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Several conditions could lead to ATN, but two significant groups were usually described: (1) ischemia-related, as observed during marked hypotension/shock conditions, such as acute pancreatitis and trauma, and (2) nephrotoxic-related agents (e.g., drugs (gentamycin, cisplatin, methotrexate), hemoglobin, myoglobin). As per the COVID-19 infection, ATN nowadays represents a well-described complication of COVID-19 hospitalized patients and the most common histomorphological pattern leading to AKI [ 101 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 ]. In our series, we observed a relevant rate of ATN in different phases (from active necrosis to later regenerative stages), and, according to the literature, it was the main pattern related to AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Several conditions could lead to ATN, but two significant groups were usually described: (1) ischemia-related, as observed during marked hypotension/shock conditions, such as acute pancreatitis and trauma, and (2) nephrotoxic-related agents (e.g., drugs (gentamycin, cisplatin, methotrexate), hemoglobin, myoglobin). As per the COVID-19 infection, ATN nowadays represents a well-described complication of COVID-19 hospitalized patients and the most common histomorphological pattern leading to AKI [ 101 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 ]. In our series, we observed a relevant rate of ATN in different phases (from active necrosis to later regenerative stages), and, according to the literature, it was the main pattern related to AKI.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of kidney involvement in COVID-19 appears to be multifactorial. Thus far, data suggest effects of direct viral infection (viral tropism to the renal system), hypoxia, inflammatory syndrome-mediated injury, hemodynamic instability, vascular injury, and hypercoagulable state [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of them describe acute kidney injury (AKI) in patients without previous renal impairment [ 7 , 8 , 9 , 10 ]. Data concerning the prevalence of AKI in hospitalized patients with COVID-19 vary from 0.5% to 46% [ 4 , 9 , 11 ]. In a large multicenter study, AKI was reported in 36.6% of 5449 adult patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the indirect impact of the pandemic's effects on chronic disease management, delivery of health services, modifications in health behaviors, and rapid attention to acute complications has not been well quantified. Patients with COVID-19 experience deterioration of cardiovascular and renal systems, both of which are causes of serious complications in presence of diabetes and obesity [8,33]; treatments must be monitored very carefully, keeping in mind that their adhearance and duration is critical for reaching the theraputical goal [34]. Very recently, an international panel of experts have emphasized that up to 50% of people who have died from COVID-19 had metabolic and vascular disorders; therefore, patients with diabetes and obesity need to be carefully managed and properly treated, now more than ever [35].…”
mentioning
confidence: 99%